Kekerasan dalam Film “Galaksi” (Analisis Isi Kualitatif) - Arsyadani, Robby; Hariyati, Farida; Rahmawati, Yulia (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2024)
The movie Galaksi is a movie adapted from Poppi Pertiwi's novel is a movie that tells about life and romance in high school. In the movie, there are many scenes of violence and this research aims to describe the forms of violence contained in the movie "Galaksi" which is popular on Netflix. This study uses the theory of violence by Weiner, Zahn and Sagi with a qualitative approach and the research method used is qualitative content analysis. The results showed that in this movie the dominant indicator of violence is physical violence in the form of beatings, beatings. Then there is also psychological violence and sexual violence. This research is expected to be a reference material for further researchers in analyzing forms of violence in films. Keywords: Violence, Content Analysis, Galaksi Movie.